The Co-Production of Intensive Services of Knowledge and Value Creation: An Analysis of Relations between Companies - Rabelo, Joselia Oliveira (2017)
The objective of this research was to identify and describe how clients and the suppliers technical and business expertise influence the coproduction and the results in the creation of economic and relational value in knowledge intensive services. In order to understand the relationship between these variables, a qualitative research was adopted, due to its exploratory focus and analyzes of the phenomenon from different perspectives clients, suppliers and the interaction between them. The interviews were based on co-production theory, its antecedents and impact on the value creation. Nine interviews were conducted with managers of different types of knowledge intensive services - Human Resource Consultancy, Software and Architecture and Engineering. The results showed that complexity, customization and strategic relevance of the solution motivate the customer to participate in the coproduction. The results of coproduction are optimized when customers and suppliers interact and share their expertise throughout the phases of diagnosis and execution of the solution, which positively influences the clients perception of value. The results pointed that co-production increases interaction and exchange of technical and businesses expertise between supplier and customer and that it favors coproduction. The customer participation in the co-production and the exchange of expertise with the supplier have positive effects on both economic and relational value. Finally, we observed that customers perceive the solution more broadly with a set formed by functional benefits of the solution and the relational processes with their suppliers.